Bangka Sago as A Superior Starch Source: Processing, Morphology, Chemical Properties, and Heavy Metal Content - Shafira Pratiwi; Edi Santosa; Mochamad Hasjim Bintoro (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Indonesia has significant potential for food diversification through the development of sago as an alternative carbohydrate source. This study aims to analyze the processing methods, morphological characteristics, chemical properties, and heavy metal content of local sago in Bangka and Bangka Tengah Regencies. The research was conducted across six villages from November 2023 to March 2024, with chemical and heavy metal testing performed in accredited laboratories. The results indicate that modern processing methods produce high quality starch with a starch content ranging from 79.06% to 83.73% and heavy metal levels such as tin (Sn), lead (Pb), and cadmium (Cd) below the established safety limits, making it safe for consumption. Morphologically, habitat differences influence the physical characteristics of sago, such as trunk height, bark thickness, and leaf area, which affect starch productivity. The study also identifies that environmental factors, including nutrient availability and soil moisture levels, influence the chemical composition of sago. This research provides a scientific foundation for the integrated management of sago, supporting national food diversification efforts and opening opportunities for the development of sago based products that meet national quality standards (SNI) with an environmentally friendly approach. These findings are relevant for stakeholders in optimizing sago's potential as a strategic commodity contributing to national food security. Keywords: Food diversification, Heavy metal, Sago, Starch content, Sustainable agriculture.